Between reason and revelation : twin wisdoms reconciled : an annotated English translation of Nasir-i Khusraw's Ktab-i Jami al-hikmatayn /: twin wisdoms reconciled : an annotated English translation of Nasir-i Khusraw's Ktab-i Jami al-hikmatayn. (2012) - Nāṣir-i Khusraw, 1004-approximately 1088
No abstract available